Legal Review of the Transfer of Waqf Land Functions for Commercial Purposes - Aisyah Aisyah; Syafruddin Syafruddin; Hediyanto Harahap (Leges Privatae, 2025)
Increasing global awareness of the climate crisis has driven a paradigm shift in development towards a sustainability-oriented green economy. Indonesia, as a party to the Paris Agreement and an implementer of the Sustainable Development Goals, is obliged to integrate sustainability principles into its investment policies. Legal certainty is a key pillar to create a stable and predictable investment climate, especially in long-term sectors such as renewable energy, sustainable natural resource management, and environmentally friendly infrastructure. This research uses normative juridical methods with legislative, conceptual, and comparative approaches, examining Law No. 25 of 2007, Law No. 32 of 2009, as well as international best practices such as the EU Taxonomy and Singapore's Green Finance Action Plan. The results of the study show that even though Indonesia already has a Green Taxonomy, its implementation is still limited, hampered by regulatory disharmony, weak institutional capacity, and the risk of greenwashing. The recommendations included the establishment of a nationally binding green taxonomy, coordination of central-regional policies, competitive legal and fiscal incentives, and firm law enforcement. This effort is expected to strengthen the competitiveness of Indonesia's green investment at the global level while ensuring a balance between economic growth, environmental protection, and social welfare